ChemInform Abstract: Photoredox Cross‐Coupling: Ir/Ni Dual Catalysis for the Synthesis of Benzylic Ethers. Issue 46 (November 2015) - Karakaya, Idris; Primer, David N.; Molander, Gary A.
Abstract The photoredox cross‐coupling of α‐alkoxymethyl trifluoroborates with aryl bromides is achieved under mild conditions using a combination of an iridium photoredox catalyst and a nickel cross‐coupling catalyst.